The effects of natural disasters on price stability in the euro area - John Beirne; Yannis Dafermos; Alexander Kriwoluzky; Nuobu Renzhi; Ulrich Volz; Jana Wittich (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
This paper investigates the impact of natural disasters on price stability in the euro area. We estimate panel and country-specific structural vector autoregression (VAR) models by combining estimated damages of disaster events with monthly data for the Harmonised Index of Consumer Prices (HICP) for all euro area countries over the period 1996-2021. Besides estimating the effect on overall headline inflation, we examine effects on its 12 main sub-indices and further sub-categories of food price inflation. This allows us to disentangle differences in the direction and strength of price effects across consumption categories. Our results suggest significant positive effects of natural disasters on overall headline inflation, with diverging results at the sub-index level. Positive inflation effects are particularly pronounced for prices of food and beverages, while negative effects prevail for other sub-indices. Our country-specific results suggest heterogenous inflation effects of natural disasters across different countries. A key implication of our findings is that climate change is likely to make it increasingly difficult for the European Central bank to achieve its inflation target.
Keywords: E31; E52; Q54; 330; Natural disasters; climate; inflation; monetary policy; European CentralBank